Evropske integracije i multirazinsko upravljanje / EU Integrative Processes and Multilevel Management - Sadiković, Elmir (Pregled: časopis za društvena pitanja / Periodical for social issues, 2016)
In the past three decades, the processes of globalization, market liberalization and European integration had significantly changed the traditional role of the state. Contrary to the state centralism, contemporary political and economic circumstances produce a specific form of political management, which, compared to a traditional hierarchical government, manifests in various forms of cooperation and coordination between different levels of territorial organization of government, from local communities to the European institutions. With the introduction of the principle of subsidiarity in the Treaty on European Union in 1992, as a fundamental principle of the division of powers between different levels of government, and the constitutional decentralization in all countries of Western Europe in the last three decades, the concept of the multilevel governance has become an important tool for an analysis of the complexity of relations between different levels of territorial management.